A Social-Ecological Approach to Studying Variation in Urban Trees and Ecosystem Services in the National Municipal District of Santo Domingo, Dominican Republic - Meléndez-Ackerman, Elvia J.; Pérez, Mervin E.; Espinal, Ana B. Pou; Caballero, Claudia; Cortés, Leonardo; Bonilla-Duarte, Solhanlle; Bauer, Gerald; Martínez Guridy, José M.; Arendt, Wayne J.; Nowak, David J. (Frontiers in Sustainable Cities, 2022)
Maintaining a diverse urban forest that provides ecosystem services can promote urban sustainability and resilience to environmental change. Around the world, cities have taken to inventorying their urban trees and quantifying their ecosystem services but more so in industrialized counties than in Latin America. Here we describe the results of an i-Tree inventory that established 206 survey plots in the National Municipal District of Santo Domingo (NMDSD). We used social-ecological theory to evaluate potential factors that may influence urban forest structure, composition, and ecosystem services diversity across three wards with distinct social and urban characteristics. Rarefaction curves showed a diverse urban forest dominated by non-native trees that have ornamental and medicinal uses. Wards differed in species composition with palms being particularly dominant in Wards 1 and 2 where the proportion of low-income houses is smaller. Ward 1 supports high-income residential areas and Ward 3 is the area with higher population and housing densities and lower income residents. On average, we found no significant differences among wards in tree species richness, average dbh, leaf area, and percent tree cover per plot. Trees in Ward 2 were taller, on average, than those in Ward 1 but were comparable to those in Ward 3. Likewise, tree density per plot was highest in Ward 2, followed by Ward 1 and Ward 3. Despite these significant differences in stem densities, average values in four ecosystem services involving measures of carbon, rainfall, and contaminants (C-sequestration, C-storage, avoided runoff, and removal of air pollutants) were non-significant across wards. We found disproportionately more street trees in Ward 1 relative to Wards 2 and 3 and more trees in public spaces in Wards 1 and 2 relative to Ward 3. Evidence for the luxury effect on tree distribution in the NMDSD was subtle and manifested mostly through differences in species composition and tree distribution across public and private domains as well as the amount of planting space. Overall results point to inequalities in the potential of reforestation among NMDS wards and an overabundance of non-native species, which should guide urban forest management with ecosystem services and conservation goals.